1999
DOI: 10.1149/1.1392558
|View full text |Cite
|
Sign up to set email alerts
|

Complete Analytical Solutions of Film Planarization during Spin Coating

Abstract: To offer a simple set of equations to designers and researchers for describing the degree of planarization (DOP), a first complete analytical solution of film planarization during spin coating is presented. The analytical solutions are suitable for an isolated feature and periodic features in the whole range of ο2 . The governing dimensionless parameter ο2 represents the ratio of centrifugal force to surface tension force during spin coating. For ο2→0 , surface tension is infinite, and the film is planar.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…The geometry and the location of the surface asperities to be planarized are determinant as well. [26][27][28][29][30][31][32] In this paper, we present an original strategy to create a modulable polymer surface architecture at the nanometer scale. The method involves adsorption of macromolecules on a polymer surface followed by spin-coating of an appropriate solution.…”
Section: Introductionmentioning
confidence: 99%
“…The geometry and the location of the surface asperities to be planarized are determinant as well. [26][27][28][29][30][31][32] In this paper, we present an original strategy to create a modulable polymer surface architecture at the nanometer scale. The method involves adsorption of macromolecules on a polymer surface followed by spin-coating of an appropriate solution.…”
Section: Introductionmentioning
confidence: 99%
“…(6), we learn that ≪ 1. The latter implies that the conditions in our system correspond to a surface-tension-dominated regime, which leads to a practically planar fluid-gas interface (see 32 for a case where Ω 2 ≈ 10 −2 ). Indeed, we find that TLD films of thickness values in the range between w = 50 nm and 270 nm acquire a peak-to-peak undulation depth H on the order of 10 −5 –10 −7 in units of w − q , i.e., much smaller than 1 nm (see Supplementary Material for more details).…”
Section: Resultsmentioning
confidence: 88%
“…Useful insight into the relevant in-plane length scale for the flow phase (λ flow ) may be obtained from the approximate analytical solutions of refs and for the flow phase. The authors show that the flow over a radially symmetric step located at x = 0 may be constructed from a set of three linearly independent terms which decay as exp(−α| x |/λ flow ).…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that substrate topography leads to a disturbance of the surface of the spin-coated film. [7][8][9][10][11][12][13][14][15][16] The effect impairs the flatness or planarity of the final film and has long been of concern to the semiconductor industry. Previous work has shown that for large (≥ O(10 µm)) features, this relationship strongly depends on the local direction and rate of fluid flow during spin coating 17,18 (see figure 1).…”
mentioning
confidence: 99%
See 1 more Smart Citation